Developing of creativity – based learning. to creativity dramatic Arts. For grade 10 students. - Manomai, Prasittiphonn (Journal for Developing the Social and Community, 2023)
The objectives of this research were: 1.) to develop creative learning management as a base for creative thinking in dramatic arts. To be effective according to criteria 70/70 2.) To compare creativity in dramatic arts with creative learning management as a base. For students in grade 4 with a criteria of 70 percent 3.) To study the satisfaction of creative learning as a base for creativity in dramatic arts. For grade 10 students, the sample group was 33 students in grade 10 students, 2nd semester of the academic year 2021, 1 classroom, totaling 33 people, obtained by group randomization. The tools used in the research consisted of: 1.) a creative learning management plan based on 5 steps of 7 plans; 2.) an assessment form for creativity in dramatic arts; manage learning The statistics used in the data analysis were percentage, mean, standard deviation. confidence value Consistency The results of the research were as follows: 1.) Creative learning management as the base. Effective 97.13/91.86 2.) After creative learning management as a base, For grade 10 students are creative in dramatic arts 88.76 3.) grade 10 students who receive creative learning as a base are satisfied with Creative learning as a whole is at the highest level.